Flavonoid compound of red fruit papua and its derivatives against sars-cov-2 mpro: An in silico approach - Agus Dwi Ananto, Harno Dwi Pranowo, Winarto Haryadi, Niko Prasetyo (Journal of Applied Pharmaceutical Science, 2024)
In the past years, the world has experienced a profound impact due to the abrupt appearance of a new virus (COVID-19), presenting a significant threat to human health. Currently, there exists no widely established treatment for COVID-19 that proves consistently effective, but many studies have implemented drug repurposing and the use of herbal medicines. The potential of antiviral compounds from natural products can be predicted through an in silico approach. This study aimed to determine and design flavonoid compounds from red fruits and their derivatives that have the potential to suppress the SARS-CoV-2 Mpro, ensuring a stable molecular framework and adhering to a standard pharmacokinetic profile. The study started with molecular docking using a lead compound followed by Molecular dynamics (MD) simulation up to 100 ns and pharmacokinetic prediction. The analysis of docking outcomes reveals that among flavonoid compounds, quercetin 3’-glucoside exhibits the most favourable binding energy value. Furthermore, the identification of hydrogen bonds with amino acid residues Asn142 and Cys145 provides additional rationale for selecting this compound as a pivotal candidate in the design of novel derivatives. The molecular docking procedure and subsequent MD simulations were conducted utilizing the Yasara-structure software. Furthermore, the evaluation of the pharmacokinetic profile was performed utilizing pkCSM ADMET to gain insights into the compound’s absorption, distribution, metabolism, excretion, and toxicity characteristics. According to the docking outcomes, among the 225 newly designed compounds, the ligand with code SR133 demonstrated the most favourable binding energy of −8.0950 Kcal/mol, surpassing the reference compound. Subsequent MD simulation analysis indicates that this ligand demonstrates good stability. The presence of hydrogen bonds in the active site of SARS-CoV-2Mpro involving the main amino acid residues Asn142 and Cys145 further clarifies that this new compound has excellent inhibitory potential. The pharmacokinetic prediction of SR133 shows that this compound has a good pharmacokinetic profile and is worth proposing as a new drug candidate.
Keywords: Docking, MD simulation, pharmacokinetic profile, SARS-CoV2 Mpro, herbal medicine